Thermodynamic Analyses of Superconducting Gap Structures and Pairing Symmetries of Molecular Charge-Transfer Salts - Nakazawa, Yasuhiro; Imajo, Shusaku (Butsuri, 2023)
High-resolution heat capacity measurements at low temperatures in magnetic fields are effective for examining gap structures and the pairing symmetries of superconductivity. Angle-resolved heat capacity measurements under in-plane magnetic fields for a series of molecules-based superconductors have revealed that dimer-Mott type compounds show d-wave paring with line-nodal gap structure. The gap symmetry changes from dxy wave to dx2－y2+s± wave depending on dimerization and frustration of the dimer lattice, even though they are in the same superconducting phase in the dimer-Mott phase diagram. In contrast, a non-dimeric compound shows anisotropic full-gapped behavior. The difference in gap structure can be understood based on the difference in their pairing interactions originating from electron correlations.